ANALISIS EKONOMI, SOSIAL DEMOGRAFI DAN LINGKUNGAN DARI FOOD LOSS/ WASTE (FLW) DI INDONESIA - Nurhasanah, Neli; Budiono, Budiono; Hermawan, Wawan (Bina Ekonomi, 2025)
Food waste, also known as food loss/waste (FLW), is an important issue in Indonesia due to its huge impact on food security, the economy, and the environment. Almost half (41.7 percent) of waste in Indonesia comes from food waste, making the country the second largest contributor to food waste globally. Each individual contributes to an average of 300kg of food waste annually in Indonesia. This analysis aims to understand the economic and socio-demographic dimensions associated with FLW in Indonesia. The study analyzed panel data in Indonesia from 34 provinces over 4 years (2019-2022) using quadratic regression models and Ordinary Least Square (OLS) estimation methods. The analysis found that GRDP per capita, Consumer Price Index (CPI), population aged 15-64 years, and population aged over 65 years had a significant effect on FLW per capita in Indonesia over the period 2019-2022. In Indonesia, there is no significant influence between the variables of average monthly per capita expenditure on food, the proportion of male and female population, and average years of schooling on per capita food waste generation. The peak point shows that the maximum value of FLW per capita is around 40.85kg/capita/year at the level of GRDP per capita of IDR 89,296,130/capita/year. This research opens up opportunities for further studies on other factors contributing to FLW in Indonesia such as psychological, environmental, and cultural.